Pharmacotherapy in bronchiolitis at discharge from emergency departments within the Pediatric Emergency Research Networks: a retrospective analysis. (August 2019) - Jamal, Alisha; Finkelstein, Yaron; Kuppermann, Nathan; Freedman, Stephen B; Florin, Todd A; Babl, Franz E; Dalziel, Stuart R; Zemek, Roger; Plint, Amy C; Steele, Dale W; Schnadower, David; Johnson, David W; et al.
Summary: Background: Clinical guidelines advise against pharmacotherapy in bronchiolitis. However, little is known about global variation in prescribing practices for bronchiolitis at discharge from emergency departments. We aimed to evaluate global variation in prescribing practice (ie, inhaled salbutamol, or oral or inhaled corticosteroids) for infants with bronchiolitis at discharge from emergency departments. Methods: We did a planned secondary analysis of a multinational, retrospective cohort study of the Pediatric Emergency Research Networks. Previously healthy infants (aged <12 months) who were discharged with bronchiolitis between Jan 1 and Dec 31, 2013 from 38 emergency departments in Australia and New Zealand, Canada, Spain and Portugal, the UK and Ireland, and the USA were included. The primary outcome was pharmacotherapy prescription at discharge from the emergency department. Secondary outcomes were revisits to the emergency department or hospitalisations for bronchiolitis within 21 days of discharge. Findings: Of 1566 infants discharged from the emergency department, 317 (20%) were prescribed pharmacotherapy. Corticosteroid prescriptions were infrequent, ranging from 0% (0 of 68 infants) in Spain and Portugal to 6% (25 of 452) in the USA. Salbutamol prescriptions ranged from 5% (22 of 432) in the UK and Ireland to 32% (146 of 452) in the USA. Compared with the UK and Ireland, the odds of prescription of pharmacotherapy were increased in Spain and Portugal (odds ratio [OR] 9·22, 95% CI 1·70–49·96), the USA (8·20, 2·79–24·11), Canada (5·17, 1·61–16·67), and Australia and New Zealand (1·21, 0·36–4·10). After adjustment for clustering by site, pharmacotherapy at discharge was associated with older age (per 1 month increase; OR 1·23, 95% CI 1·16–1·30), oxygen saturation (per 1% decrease from 100%; 1·09, 1·01–1·18), chest retractions (1·88, 1·26–2·79), network (p=0·00050), and site (p<0·00090). 303 (19%) of 1566 infants returned to the emergency department and 129 (43%) of 303 were hospitalised. Discharge pharmacotherapy was not associated with revisits (p=0·55) or subsequent hospitalisations (p=0·50). Interpretation: Use of ineffective medications in infants with bronchiolitis at discharge from emergency departments is common, with large differences in prescribing practices between countries and emergency departments. Enhanced knowledge translation and deprescribing efforts are needed to optimise and unify the management of bronchiolitis. Funding: None.